From 'perplexities of plagiarism' to 'building cultures of integrity' : A reflection on fifteen years of academic integrity research, 2003-2018. - Bretag, Tracey (HERDSA Review of Higher Education v.6 p.5-35, 2019)
Despite the relatively recent interest in academic integrity, Australian researchers have provided global leadership in reconceptualising academic integrity as a complex, multi-stakeholder responsibility which goes well beyond students plagiarising or cheating. The work of Australian researchers, while influenced by large-scale surveys of students' self-reported cheating in the U.S., and technology-driven responses to plagiarism in the U.K., has been driven by the radically altered higher education landscape over the last two decades. Most Australian research has contextualised academic integrity as a teaching and learning issue, foregrounding the importance of students' learning, rather than students' character. Recent threats to academic integrity, such as contract cheating, have once again focussed attention on the role of governments, regulatory bodies and institutions to adequately resource teaching and provide critical support for vulnerable student cohorts. [Author abstract]